New Possibilities of Robot Arm Motion Simulation - Rengevic, Alexander; Kumicakova, Darina (Communications - Scientific letters of the University of Zilina, 2016)
The importance of computer simulations of the industrial robot arm motions at the technological scene becomes more important especially in connection with industrial applications of the new types of robot arm kinematic structures or with solving the human robot safety collaboration in industry. The article is aimed at the simulation of the basic (primitive) tasks executed by industrial robot with utilization of software packages of the ”open-source“ platform ROS. ROS is the software of modular architecture that extends the capabilities of the different robot types programming and controlling.